The criminal and civil ways to protect the minor against international abduction. Its coexistence in the European judicial area - Sabido Rodríguez, Mercedes (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Protection against international child abduction is articulated through different channels. The international conventions and, more recently, the European texts are intended to regulate the instruments through which civil protection is articulated. Through it, the restitution of the minor is sought or, where appropriate, the recognition and/or execution of a decision adopted in another State regarding parental responsibility. Along with this route, national legislation contemplates the crime of international child abduction, through which the criminal protection route is articulated against this type of crime. The coexistence of both channels, which use optional and cumulative, is not exempt from difficulties, particularly for the sake of the functioning of the European judicial area. A space governed by the principles of equality and prohibition of discrimination, in which freedom of movement and residence is configured as a basic freedom and where the principle of mutual recognition is configured as a cornerstone of the cooperation system in both the civil and social spheres. in the prison. An approach to the issues raised by the existence of this double path of protection in the European judicial space is the object of this study.
Keywords: International Child abduction; criminal protection; civil protection; European Union